2007
DOI: 10.1177/1177391x0700100002
|View full text |Cite
|
Sign up to set email alerts
|

FTY720 Story. Its Discovery and the following Accelerated Development of Sphingosine 1-Phosphate Receptor Agonists as Immunomodulators Based on Reverse Pharmacology

Abstract: Fingolimod (FTY720) is the first of a novel class: sphingosine 1-phosphate (S1P) receptor modulator and is currently in phase 3 clinical trials for multiple sclerosis (MS). FTY720 was first synthesized in 1992 by chemical modification of an immunosuppressive natural product, ISP-I (myriocin). ISP-I was isolated from the culture broth of Isaria sinclairii, a type of vegetative wasp that was an ‘eternal youth’ nostrum in traditional Chinese medicine. ISP-I is an amino acid having three successive asymmetric cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
77
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 83 publications
0
77
0
Order By: Relevance
“…FTY720 {2-amino-2-[2-(4-octylphenyl)ethyl]propane-1,3-diol} is structurally similar to sphingosine and the lead compound from which it was derived, ISP-1 (myriocin), was isolated from the culture broth of Isaria sinclairii (25). Also known as Fingolimod, or by the trade name Gilenya TM , FTY720 is currently used clinically to quell the symptoms and slow the progression of multiple sclerosis.…”
Section: Fty720mentioning
confidence: 99%
“…FTY720 {2-amino-2-[2-(4-octylphenyl)ethyl]propane-1,3-diol} is structurally similar to sphingosine and the lead compound from which it was derived, ISP-1 (myriocin), was isolated from the culture broth of Isaria sinclairii (25). Also known as Fingolimod, or by the trade name Gilenya TM , FTY720 is currently used clinically to quell the symptoms and slow the progression of multiple sclerosis.…”
Section: Fty720mentioning
confidence: 99%
“…These receptors are targets for the drug pFTY720 (fingolimod), which is the first oral therapy for relapsing remitting multiple sclerosis (Kappos et al, 2010). The proposed mechanism of action for pFTY720 is reported as being dependent on internalisation of S1PRs in T cells, which limits their S1P-mediated egress from lymph nodes and thus attenuates the inflammatory response in the brains of multiple sclerosis patients (Adachi and Chiba, 2008). Importantly, a number of studies have now demonstrated that compounds such as pFTY720 can also regulate neuronal and glial cell function (Balatoni et al, 2007;Choi et al, 2011;Fischer et al, 2011;Osinde et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Myriocin was isolated from the culture broth of a type of entomopathogenic fungus (Isaria sinclairii), which was an eternal youth nostrum in traditional medicine. 57 Showing positive results in both in vitro and in vivo screening, myriocin was modified through a series of steps to yield fingolimod, code named at the time FTY720. 58 Mechanistic analysis showed that fingolimod (FTY720) also affects lymphocyte migration, and it is the first oral therapeutic approved by the Food and Drug Administration (2010) for treatment of relapsing forms of MS at a dose of 0.5 mg given orally once a day.…”
Section: Fingolimod (Gilenya)mentioning
confidence: 99%